GeSn on Insulators (GeSnOI) Toward Mid-infrared Integrated Photonics - Wang, Xiaoxin; Cuervo Covian, Alejandra; Je, Lisa; Fu, Sidan; Li, Haofeng; Piao, James; Liu, Jifeng (Frontiers in Physics, 2019)
In recent years, Ge and Ge1-xSnx materials and devices have achieved rapid progress in integrated photonics. However, conventional heteroepitaxy of active photonic devices compromises the area on Si for CMOS electronics, limiting the scale of integration. Furthermore, it is not possible to grow GeSn epitaxially on amorphous and/or flexible substrates towards 3D photonic integration in mid infrared (MIR) regime. Here we present low-temperature crystallization of direct bandgap, high crystallinity Ge1-xSnx (0.08<x<0.26) on amorphous dielectrics insulators (GeSnOI) towards 3D and flexible MIR integrated photonics. Utilizing eutectically-enhanced crystallization, an extraordinarily large average grain size of 100 m has been achieved in blanket GeSn films crystallized on SiO2 layers, flexible glass, and polyimide substrates alike. Furthermore, using Sn nanodot enhanced composition enhancement (NICE), we have achieved an average Sn composition as high as 26 at. % to further extend the optical response of GeSn towards =3-5 m. The achieved Sn composition of 8-26 at.% far exceeds that of the equilibrium solubility limit of < 1 at.%, even though the crystallization temperature of 350-450 °C far exceeds the typical epitaxial growth temperature of GeSn. This result indicates that crystallization from a-GeSn may offer better metastability compared to direct epitaxial growth of GeSn. Attesting to the high crystallinity, a peak optical gain of 2900 cm-1 with a lifetime approaching 0.1 ns is achieved at λ=2200-2350 nm at 300 K. The gain lifetime is on the same order as epitaxial GeSn, and it is >100x longer than the direct gap transition in Ge, confirming the indirect-to-direct band gap transition in GeSn at 9 at. Sn composition. Moreover, a prototype p-GeSn/n-Si photodiode from a-GeSn crystallization achieves 100 mA/W responsivity at =2050 nm and T=300 K, approaching the level of some commercial PbS detectors. The device also demonstrates photovoltaic behavior and a low dark current density of 1 mA/cm2 at -1V reverse bias, comparable to epitaxial Ge/Si photodiodes. These results indicate that crystallization of GeSnOI offers a promising solution for active devices towards 3D MIR photonic integration and/or MIR photonics on flexible substrates.